THE CRISIS OF HUMANITY: OR, WHAT IF WE HAVE NEVER BEEN HUMAN? - Dodd, Adam (History & Theory, 2017)
This collection of nine essays brings together a variety of responses to the question of the 'nonhuman turn' within the humanities and the social sciences, understood broadly as a developing concern with overcoming anthropocentrism in its diverse manifestations. Emerging from The Nonhuman Turn conference held at the University of Wisconsin-Milwaukee in 2012, which was hosted by the Center for 21st Century Studies, it represents the first attempt to account for and consolidate the many intellectual approaches and developments that may now be regarded as constituting the nonhuman turn. The nonhuman turn is contextualized as both 'yet another' turn but also a necessary one, and as something critically distinct from 'the posthuman turn'-whereas the posthuman turn is concerned with what comes after the human (ways of being, ways of thinking), the nonhuman turn insists (according to editor Richard Grusin) that 'we have never been human.' My reading of this volume suggests that this claim is not borne out across the chapters it contains, and that the notion that we have never been human, though a noble gesture to Bruno Latour's widely lauded claim that 'we have never been modern,' does not enable a new philosophy, nor does it advance the two primary streams of philosophical thought featured here: object-oriented ontology (OOO) and new materialism.